Research and Practice on the "One Core, Two Wings" Innovation Talent Cultivation Model for Mechanical Engineering in the Context of New Engineering Education - Shi, Dongyan; Song, Dening; Ying, Lixia; Wang, Jiuqiang (Journal of Educational Research and Policies, 2024)
Facing the challenges brought by the new round of technological revolution and industrial transformation under the context of New Engineering Education, this paper proposes an innovation talent cultivation model for mechanical engineering called "One Core, Two Wings." This model aims to comprehensively enhance students' overall quality and innovation ability by constructing a curriculum system that integrates both general and specialized knowledge with a spiral development approach ("One Core"), along with a hybrid teaching organization and a practice-driven teaching model ("Two Wings"). The paper elaborates on methods for course reconstruction, including building a networked bridge connecting multi-disciplinary knowledge fragments, optimizing the integration of general engineering courses, and incorporating frontier knowledge from mechanical engineering into the specialized education curriculum. It also introduces a hybrid teaching and research organizational structure, as well as a practice-driven teaching mode, where real-world engineering problems, cases, projects, and research outcomes from industry are brought into classroom teaching through a collaborative model of industry-university cooperation. Through these innovative measures, this paper aims to provide a systematic solution for the cultivation of mechanical engineering talents, as well as for the wider New Engineering Education talent training, to foster interdisciplinary and innovative talents capable of leading technological innovation and solving complex engineering problems.